Chromosomal Speciation in the Genomics Era: Disentangling Phylogenetic Evolution of Rock-wallabies - Potter, Sally; Bragg, Jason G.; Blom, Mozes P. K.; Deakin, Janine E.; Kirkpatrick, Mark; Eldridge, Mark D. B.; Moritz, Craig (Frontiers in Genetics, 2017)
The association of chromosome rearrangements with speciation is well established, and there is a long history of theory and evidence relating to “chromosomal speciation”. Genomic sequencing has the potential to provide new insights into how reorganization of genome structure promotes divergence, and in model systems has demonstrated reduced gene flow in rearranged segments. However, there are limits to what we can understand from a small number of model systems, which each only tell us about one episode of chromosomal speciation. Progressing from patterns of association between chromosome (and genic) change, to understanding processes of speciation requires both comparative studies across diverse systems and integration of genome-scale sequence comparisons with other lines of evidence. Here we showcase a promising example of chromosomal speciation in a non-model organism, the endemic Australian marsupial genus Petrogale. We present initial phylogenetic results from exon-capture that resolve a history of divergence associated with extensive and repeated chromosome rearrangements. Yet it remains challenging to disentangle gene tree heterogeneity caused by recent divergence and gene flow in this and other such recent radiations. We outline a way forward for better integration of comparative genomic sequence data with evidence from molecular cytogenetics, and analyses of shifts in the recombination landscape and potential disruption of meiotic segregation and epigenetic programming. In all likelihood, chromosome rearrangements impact multiple cellular processes and these effects need to be considered together, along with those of genic divergence. Understanding the effects of chromosome rearrangements together with genic divergence will require development of more integrative theory and inference methods. Together, new data and analysis tools will combine to shed light on long standing questions of how chromosome and genic divergence promote speciation.